Physical Properties of Soy-Phosphate Polyol-Based Rigid Polyurethane Foams - Hongyu Fan; Ali Tekeei; Galen J. Suppes; Fu-Hung Hsieh (International Journal of Polymer Science)
Water-blown rigid polyurethane (PU) foams were made from 0–50% soy-phosphate polyol (SPP) and 2–4% water as the blowing agent. The mechanical and thermal properties of these SPP-based PU foams (SPP PU foams) were investigated. SPP PU foams with higher water content had greater volume, lower density, and compressive strength. SPP PU foams with 3% water content and 20% SPP had the lowest thermal conductivity. The thermal conductivity of SPP PU foams decreased and then increased with increasing SPP percentage, resulting from the combined effects of thermal properties of the gas and solid polymer phases. Higher isocyanate density led to higher compressive strength. At the same isocyanate index, the compressive strength of some 20% SPP foams was close or similar to the control foams made from VORANOL 490.